Creative movement in 3rd grade general music classroom: using a Dalcroze plastique anime to demonstrate ¾ meter - Bachand, Jodi (My University, 2025)
The topics demonstrated in this report are focused on student creative movement in triple meter using the Dalcroze approach. The Dalcroze approach utilizes students’ becoming a part of the music making while using their hearing and movement skills. These lessons incorporated Dalcroze-inspired approach using different movement warmups, experiencing meter in different ways, identifying different parts of music, and developing a plastique anime with a group of other students to demonstrate their response to music. I designed these lessons for my students based on new ideas I gained from study during my master’s program in the areas of Dalcroze in music symposium. I have noticed that as a teacher, my students experienced moving with a steady beat, but did not experience different types of meters or being able to hear or feel what meter they were moving in. By using the different techniques learned in the Dalcroze method, students were able to use new movement activities that previously have not been utilized, new listening skills to become part of music making, and use a different outlet for their creativity. Over the course of my Masters’ degree, I have expanded my knowledge and understanding of a different methodology and listening in my World Music class as well as moving and listening techniques in the Dalcroze course helped me create lessons based on listening and moving. Being certified in the Orff-Schulwerk methodology has been extremely beneficial to my teaching, but I am always striving to become a more skilled teacher to give more experience to my students. When creating this creative movement unit, I wanted to use the new Dalcroze techniques I learned in symposium.
Keywords: Movement; Dalcroze